2017
DOI: 10.1088/1361-6528/aa98ee
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effect of electric fields on the mechanical property of water-filled carbon nanotubes with an application as a nanoscale trigger

Abstract: Polar water molecules would exhibit extraordinary phenomena under nanoscale confinement. By means of electric field, the water-filled carbon nanotube (CNT) that has been successfully fabricated in laboratory is expected to make distinct responses to the external electricity. Here, we examine the effect of electric field direction on the mechanical property of water-filled CNTs. It is found that the longitudinal electric field enhances but the transversal electric field reduces the elastic modulus and critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These results demonstrated that the bistability of SWCNTs can be regulated by the electric field combined with the capillary effect. Moreover, compared with previous approaches using either the mechanical [17,18,20,21] or electrical [6,7] methods, the present method is much more convenient and the response of SWCNT is much faster, i.e. in a few picoseconds.…”
Section: Collapsing Of the Swcnt-droplet Complex Under An Electric Fieldmentioning
confidence: 95%
See 1 more Smart Citation
“…These results demonstrated that the bistability of SWCNTs can be regulated by the electric field combined with the capillary effect. Moreover, compared with previous approaches using either the mechanical [17,18,20,21] or electrical [6,7] methods, the present method is much more convenient and the response of SWCNT is much faster, i.e. in a few picoseconds.…”
Section: Collapsing Of the Swcnt-droplet Complex Under An Electric Fieldmentioning
confidence: 95%
“…Interestingly, the collapsed crosssectional configuration causes a continuous reduction of the nanotube's bandgap from 0.92 eV to zero [19], which results in a semiconductor to metal transition, a perfect property for working as potential nanoswitches. The axial loading along the longitudinal direction of the CNTs can also perturb the configuration of the nanotube to change their conductivity [20,21]. However, the application of the mechanical load to the SWCNTs is cumbersome, as the loading direction and amplitude cannot be easily manipulated at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Esmaeilzadeh et al [45] discussed the effect of hydrophobicity on the water flow in a CNT. The interaction between water and CNT has been applied to design different nanodevices [21,[46][47][48][49]. Up to now, to our knowledge, there is no report on the transmission properties of an RTnS in water.…”
Section: Introductionmentioning
confidence: 99%